The transforming power of the nuns : women, religion, and cultural change in Ireland, 1750-1900 - Magray, Mary Peckham (Oxford University Press, 1998)
Challenging widely-held assumptions of 19th-century social history in Ireland, this book examines the influence of Irish nuns on the Irish Catholic cultural revolution. It claims they were not merely passive servants, but educated women at the centre of the creation of a devout Catholic culture.